2020
DOI: 10.1097/cce.0000000000000122
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Intensive Care Patient Experience With Virtual Reality—A Feasibility Study

Abstract: Background: Patients undergoing critical care can experience negative outcomes due to a variety of causes such as lack of sleep, prolonged pain, and anxiety. Our goal was to evaluate the feasibility and efficacy of using meditative virtual reality (VR) to improve the hospital experience of intensive care unit (ICU) patients.• Methods: A Google Daydream headset was used to expose ICU patients to commercially available VR applications focused on calmness and relaxation (Google Spotlight Stories and RelaxVR). Ses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 18 publications
6
52
0
Order By: Relevance
“…For the primary outcome, we found that the use of a 10-minute VR intervention resulted in a signi cant reduction of pre-operative anxiety as measured using the HADS. These ndings are in congruence with other studies using HADS to measure changes in pre-operative anxiety for VR interventions in oncology patients [32,33] and patients in intensive care [34]. Taken together, it might suggest that VR could have a role to play alleviating preoperative anxiety.…”
Section: Discussionsupporting
confidence: 90%
“…For the primary outcome, we found that the use of a 10-minute VR intervention resulted in a signi cant reduction of pre-operative anxiety as measured using the HADS. These ndings are in congruence with other studies using HADS to measure changes in pre-operative anxiety for VR interventions in oncology patients [32,33] and patients in intensive care [34]. Taken together, it might suggest that VR could have a role to play alleviating preoperative anxiety.…”
Section: Discussionsupporting
confidence: 90%
“…This study revealed that there is signi cant preoperative anxiety amongst the gynecological patients recruited, and is in congruence with other studies using HADS to measure changes in pre-operative anxiety for VR interventions in oncology patients [29,30] and patients in intensive care [31]. Surgery is a daunting experience that comes with emotional vulnerabilities.…”
Section: Discussionsupporting
confidence: 87%
“…While the pain scores collected pre-and post-VR intervention did not reveal any significantly changes, EQ-5D-3L measures further revealed that pre-operative self-reported perception of pain and discomfort and perceived health states were improved after VR intervention. This study revealed that there is significant preoperative anxiety amongst the gynecological patients recruited, and is in congruence with other studies using HADS to measure changes in pre-operative anxiety for VR interventions in oncology patients [29,30] and patients in intensive care [31]. Surgery is a daunting experience that comes with emotional vulnerabilities.…”
Section: Discussionsupporting
confidence: 87%